Valorization of spent barley grains: isolation of protein and fibers for starch-free noodles and its effect on glycemic response in healthy individuals - Shi, Pujiang; Ng Yuen Kai, Rachel; Vijayan, Poornima; Lim, Su Lin; Bhaskaran, Kalpana (Frontiers in Sustainable Food Systems, 2023)
Spent barley grains (SBG) were valorized into a spent barley protein and fibers (SBPF) ingredient. The ingredient was utilized to formulate SBPF-derived starchless noodles with a negligible glycemic response (GR) in healthy individuals, a significant reduction of 93.16% (SD = 8.07) postprandial GR after consumption when compared to conventional starch-based noodles. Their nutritional content, visual analog scale, textural property, and palatability were also evaluated. The SBPF-derived starchless noodles showed comparable hardness and springiness to the conventional starch-based noodles, but their cohesiveness and chewiness were improved. There was no significant difference in appetite and hunger ratings between the two types of foods. The overall palatability ratings for both foods were comparable. The SBPF-derived noodles were a source of nutrients (such as protein and fibers). This study has considerable potential for the development of functional food and food as medicine industries.